Nachhaltige Entwicklung : Grundlagen und Umsetzung - Hauff, Michael von (De Gruyter Oldenbourg, 2014)
This book provides an introduction to the model of sustainable development, and discusses the theoretical principles underlying weaker and stronger sustainability as well as the three dimensions of sustainability. Based on this foundation, it goes on to examine the importance of innovation, technological progress, and eco-efficiency.